Development of mango-kamias juice drink - Vergara, Jennifer Gaddi; Francisco, Ma. Leonora dL. (1999.)
A study on the development of Canned Mango-Kamias Juice Drink was undertaken. Phase I determined the most acceptable formulations of a mango-kamias juice drink and this was a blend of 70% mango juice and 30% kamias juice. Table-ripe mangoes of the Carabao variety shipped from Davao were used while the kamias fruits on the other hand, were carefully handpicked from selected kamias tree grown in the North Fairview area and Floridablanca, Pampanga. The results in Phase I showed that the nine samples from which one was to be chosen as the most acceptable formulation for the mango-kamias juice drink were significantly different from each other based on the Analysis of Variance in terms of color, appearance, odor, flavor, and overall acceptability. This made it possible for the panelists to eliminate the samples which were not acceptable due to an extreme sourness in taste. Sensory results showed that a juice blend which consisted a 70% mango and 30% kamias juice was the most acceptable formulation for the development of mango-kamias juice drink. Phase II determined the optimum ratio of juice blend to water. The formulation that was chosen in Phase I was diluted to three different ratios of juice to water which were as follows: 1:1, 1:1.5, and 1:2. Sensory results showed that the panelists preferred the sample with a 1.5 dilution factor of water. Phase III involved the processing and characterization of the canned mango-kamias juice drink. Here, the process for making mango-kamias juice drink was established and standardized by subjecting the juice drink to a thermal process of 212°F for 15 minutes. Heat penetration test was conducted and based on the calculated lethality rates and F-value obtained, the process applied was sufficiently adequate to kill the reference microorganism which was Byssochlamys fulva. Physico-chemical test results showed that the thermal process employed had minimal effects on the physico-chemical characteristics of the sample which were pH, titrable acidity, and total soluble solids content. It did however showed a significant decrease in the level of ascorbic acid content after processing of the juice drink. Such results indicate the preventive measures should be undertaken to minimize the loss of ascorbic acid content especially during preparation and extraction of the juice from the fruits, heat processing, and storage conditions. However, event though there was a decrease in ascorbic acid content of the juice after processing, results showed that the Vitamin C present in the processed juice was still more than sufficient in providing the required Vitamin C RDA of an individual per day. Results from the microbiological examinations showed that the fruit drinks produced were relatively safe for human consumption. Phase IV determined the consumer acceptability evaluation of the canned mango-kamias juice drink. The finished product was rated very good in terms of quality. The panelists liked the product very much and they are willing to drink the mango-kamias juice very often.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Fruit juices